Efektivitas Program Beasiswa Bidikmisi di Universitas Negeri Surabaya - Fauzi, Amin; Astuti, Dwi Harmani; H, Samsuruhuda (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2020)
The focus of the study is to determine the effectiveness of ˜Bidikmisi scholarship program implementation at Universitas Negeri Surabaya (Unesa). This qualitative research uses a case study approach to find wider and deeper understanding of the data collected. The data collection methods are through interviews, observations, and documentations. Research data is then analysed to define the efficacy of ˜Bidikmisi at Unesa. The results of the study imply that Unesa has implemented government policy to provide access to higher education to people with low economic backgrounds. The effectiveness of ˜Bidikmisi at Unesa is based on the accomplishment of the program objectives, explicitly (1) equitable access to education, (2) numbers of on time graduates, and (3) students increasing achievements. The result of the research data analysis has shown that Bidikmisi program is effectively implemented at Unesa. Factors inhibit to the enactment of the program at Unesa are the lack of coordination between the program managers and related units, less information to Bidikmisi recipients, incomplete monitoring and evaluation process, and less committed Bidikmisi recipients to their individual responsibility.